2015
DOI: 10.1364/optica.2.000040
|View full text |Cite
|
Sign up to set email alerts
|

Miniature multioctave light source based on a monolithic microcavity

Abstract: Optical microresonators are ideal tools for the reduction of the threshold of optical parametric oscillation based on four-wave mixing. Usually, the efficiency and bandwidth of the resonant process are interdependent due to stringent phase matching requirements leading to limitation of the bandwidth of the spectrum generated for a given pump power. We demonstrate a continuous-wave low-threshold resonant optical parametric oscillator with optical spectral span ranging from 0.36 to 1.6 μm. Harmonic generation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 91 publications
(113 reference statements)
1
45
0
Order By: Relevance
“…[65]. Recent experiments have also shown that Kerr combs can even have a multioctave spectral span [66]. Therefore, Kerr combs can be self-referenced and be useful for metrological applications.…”
Section: Ultra-stable Microwave Generationmentioning
confidence: 99%
“…[65]. Recent experiments have also shown that Kerr combs can even have a multioctave spectral span [66]. Therefore, Kerr combs can be self-referenced and be useful for metrological applications.…”
Section: Ultra-stable Microwave Generationmentioning
confidence: 99%
“…14) [258]. Similarly to generation of multioctave hyper-parametric oscillation [96], the mode-locked SRS is observed when the pumping is performed at normal GVD where the generation of the conventional Kerr frequency comb has a higher threshold.…”
Section: Global Correctionmentioning
confidence: 96%
“…For example, phase matching of the FWM process in fibers can be achieved via different mode families of the fibers [93][94][95] and, similarly, in microresonators [96]. Generation of frequency harmonics by seeding modulated light to a fiber link [97], a sub-micron silicon-on-insulator rib waveguide [98], and a coupled-resonator optical waveguides [99] have also been observed.…”
Section: Resonant Wave Mixingmentioning
confidence: 97%
See 2 more Smart Citations